Cloud Infrastructure Modernization in Enterprise Manufacturing: A Longitudinal Case Study of Digital Transformation at Mattel, Inc. - Anil kumar Thimmapuram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive case study of cloud infrastructure modernization at Mattel, Inc., examining the implementation of cloud-native solutions and DevOps practices in a global manufacturing enterprise. The article investigates the transformation of legacy systems through Google Cloud Platform (GCP) integration, Infrastructure as Code (IaC) implementation using Terraform, and containerized microservices orchestration via Google Kubernetes Engine (GKE). The article methodology encompasses both technical implementation analysis and quantitative assessment of operational metrics. Results demonstrate significant improvements across multiple dimensions, including substantial reduction in deployment errors, enhanced system performance, and accelerated time-to-market for digital solutions. The implementation of automated CI/CD pipelines through Jenkins and TeamCity yielded marked improvements in deployment efficiency while maintaining robust security protocols for PCI-DSS and GDPR compliance. This article contributes to the growing body of knowledge in enterprise digital transformation by providing empirical evidence of cloud-native architecture's impact on operational efficiency and scalability. The article findings offer valuable insights for organizations pursuing similar modernization initiatives, particularly in regulated industries requiring stringent security compliance.
Keywords: Digital Transformation; Cloud Infrastructure Modernization; Infrastructure as Code; Container Orchestration; Enterprise DevOps